DISMISSAL ARISING FROM FLOUTING COVID-19 HEALTH AND SAFETY PROTOCOLS Eskort Limited v Stuurman Mogotsi [2021] ZALCJHB 53 - CI Tshoose (Obiter, 2021)
The Labour Court judgment handed down by Tlhotlhalemaje J in Eskort Limited v Stuurman Mogotsi (JR1644/20) (2021) ZALCJHB 53 (Eskort Limited) on 28 March 2021 raised the topical issue of fairness regarding the dismissal of an employee for gross misconduct and negligence related to his failure to follow and/or observe COVID-19-related health and safety protocols put in place at the workplace (Eskort Limited supra par 1). In light of the above, the objectives of this case note are twofold. First, it examines the parameters under which the employer can discipline an employee for flouting the COVID-19 safety protocols and regulations. Secondly, it also considers the extent to which the employer can take appropriate action against an employee who wilfully refuses to obey the lawful and reasonable instructions of the employer during COVID-19 times.